2014
DOI: 10.35196/rfm.2014.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrins Patterns in Common Bean Exposed to Drought and Watered Conditions

Abstract: Drought is a major constraint for common bean (Phaseolus vulgaris L.) production in México. Dehydrins are constitutive or stress-induced proteins related with a protective role of membranes and macromolecules against denaturation, thus preventing loss of their function. In this work, seed production and patterns of dehydrins accumulation in leaves and pods were evaluated in common bean cv. ‘Otomí’ subjected to drought, as compared with well-irrigated plants. Drought applied at pod formation and seed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Nuñez- Barrios et al (2005) reported reductions of 63•3% in pod number per plant, 28•9% in seed number per plant and 22•3% in 100 seed weight in common bean grown under drought. Reduction in pod number during pod formation is critical and caused a loss of 40% in seed yield under drought (Castañeda-Saucedo et al 2009). In the present study, several lines showed favourable genotypic values for grain yield, pod number per unit area and seed number per unit area under drought and irrigated conditions, whereas the drought-sensitive lines showed poor pod development and thus smaller number of seeds per plant as drought stress continued from pod formation to physiological maturity in terminal drought stress conditions.…”
Section: Contribution Of Photosynthate Mobilization To Pod and Seed Dsupporting
confidence: 43%
“…Nuñez- Barrios et al (2005) reported reductions of 63•3% in pod number per plant, 28•9% in seed number per plant and 22•3% in 100 seed weight in common bean grown under drought. Reduction in pod number during pod formation is critical and caused a loss of 40% in seed yield under drought (Castañeda-Saucedo et al 2009). In the present study, several lines showed favourable genotypic values for grain yield, pod number per unit area and seed number per unit area under drought and irrigated conditions, whereas the drought-sensitive lines showed poor pod development and thus smaller number of seeds per plant as drought stress continued from pod formation to physiological maturity in terminal drought stress conditions.…”
Section: Contribution Of Photosynthate Mobilization To Pod and Seed Dsupporting
confidence: 43%
“…Data from several research studies has shown that plant biomarkers are differentially expressed at different stages of plant growth when exposed to the same stress condition. Castañeda-Saucedo et al ( 2014 ) reported differences in dehydrin accumulation at the seed filling and pod formation stages of common beans ( Phaseolus vulgaris L.) subjected to drought stress. In a similar experiment, Samarah and colleagues observed a more significant dehydrin accumulation in soybean seeds ( Glycine max L.) at the maturity stage compared to the developmental stage (Samarah et al 2006 ).…”
Section: Factors Influencing the Expression Of Plant Biomarkers In Cr...mentioning
confidence: 99%
“…Similar to the extent of yield-losses recorded in cereal crops, substantial yield reductions were reported in grain legume crops owing to their susceptibility to drought stress. For instance, drought stress was reported to cause up to a 50 % yield loss in several legume crops including soybean (Guttikonda et al 2014), common bean (Castañeda-Saucedo et al 2014), chickpea (Varshney et al 2014), and cowpea (Ahmed and Suliman 2010).…”
Section: Introductionmentioning
confidence: 99%